Formation of informational competence of university students in a credit system - Nasharbekova, I.S.; Tleuzhanova, K.T. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article reveals the author's approach to the organization of the process of formation of students informational competence under credit system. In this article the nature, structure, functions, development of informational competence of students were revealed and the methods for designing and pedagogical conditions were provided. The content of process's technological providing, which include the model and pedagogical technologies were proved. It is noted that the credit system of education has been recognized worldwide as one of the most important areas of integration of education with production, and as the essential component of the continuous educational system. And today it is necessary to form the elements of the new informational technologies.
Несиелік оқыту жүйесі жағдайындағы жоғары оқу орны студенттерінің ақпараттық құзырын қалыптастыру
Формирование информационной компетентности студентов вуза в условиях кредитной системы обучения
Keywords: competence; modern education; skills; technology; professional activity; educational process; professional tasks; system of knowledge; cognitive competence; information